Analysis of Factors Affecting Efficiency of UAE E-Government Procurement System - Maimunah Ali; Obaid, Faisal Obaid (International Journal of Sustainable Construction Engineering and Technology, 2022)
E-government services, including the e-government procurement platform, are a top priority for the UAE government (E-GPP). E-GPP implementation has not been studied extensively, so researchers set out to investigate how critical organisational factors affect E-GPP implementation in UAE. For the purpose of prioritising the factors that affect efficiency of Emirati Electronic Government Procurement Platform, this paper conducted an exploratory study (EEGPP). Mean values were calculated from the 206 questionnaires that were filled out. Factors such as E-GP Planning and Policies; Change Management; E-GP Training; and E-GP Service Quality were found to be moderate to high in defining the importance of each category. In addition, innovation and efficiency are reported to be moderate to high measuring factors. Also ranked each factor to prioritise and identify the most important ones.. As a guideline, the findings of this study can be used in the development of an E-government procurement strategy that is more effective.